L’opération propre de l’Esprit Saint d’après Didyme l’Aveugle - Grzywaczewski, Joseph (Vox Patrum, 2018)
The article presents the proper operation of the Holy Spirit within the Holy Trinity according to Didyme the Blind; because he lived and worked in Alexandria he is called sometimes Didyme of Alexandria. We have his treatise De Spiritu Sancto in Latin translation by Saint Jerome who adapted author’s terminology to the post-Nicaean theology. That diminishes its theological value. Didyme shows the operation of the Holy Spirit in the time of the Old Testament; he gave inspiration to the prophets, even if they ignored his existence as an individual being. When the prophets say: “the Lord said to me” they mean: the Holy Spirit. Didyme quoted some passages from the Bible concerning David and Isaiah as the men inspired by the Holy Spirit. Didyme of Alexandria underlines than the Holy Spirit helps to understand the Word of God; he completes the teaching of Christ; he grants wisdom to the faithful. The people enlightened by the Holy Spirit are able to understand the things with are not possible to understand only with purely human intellect. Following Origen, Didyme stresses that moral purity is required for receiving the gifts of the Holy Spirit because he does not operate in the souls of the sinners. The Holy Spirit introduces the faithful into the mystery of the Holy Trinity. The Holy Spirit not only makes the Christians able to understand God’s mysteries, but also he gives strength in difficult situations, as we can see it, for example in the life of Saint Stephen; he had wisdom for discussing with his adversaries and courage to die for Christ’s sake.